2019
DOI: 10.1111/peps.12366
|View full text |Cite
|
Sign up to set email alerts
|

How do employees react to leaders’ unethical behavior? The role of moral disengagement

Abstract: Concerns over unethical leader behavior persist in today's workplace. Although some employees continue to support their leaders after learning of their unethical actions, others do not. In this paper, we integrate social cognitive theory with social information processing theory to propose that the support employees give to leaders who act unethically hinges on their propensity to morally disengage.Specifically, we develop a conditional indirect effects model, wherein moral disengagement propensity mitigates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 91 publications
1
53
0
1
Order By: Relevance
“…Like Fehr et al. (), Umphress et al. also suggested that employees’ trait MDP influences their reactions, making them more likely to engage in unethical behavior.…”
Section: Strengths and Contributions To Theory And Methodsmentioning
confidence: 91%
See 4 more Smart Citations
“…Like Fehr et al. (), Umphress et al. also suggested that employees’ trait MDP influences their reactions, making them more likely to engage in unethical behavior.…”
Section: Strengths and Contributions To Theory And Methodsmentioning
confidence: 91%
“…To be sure, narrative reviews of behavioral ethics literature have emphasized the application of SIPT to explain ethics phenomena (e.g., Tenbrunsel & Smith‐Crowe, ; Treviño et al., ). Three papers within this special issue relied on SIPT to explain how employees turn to leader behavior (Fehr et al., ; Kuenzi et al., ), leader communications (Babalola et al., ), and general norms and procedures within the environment (Kuenzi et al., ) to inform their behavior (e.g., customer‐directed incivility, performance, support offered to their leaders, and unethical behavior).…”
Section: Strengths and Contributions To Theory And Methodsmentioning
confidence: 99%
See 3 more Smart Citations